Exploring the Determinants of Customer Loyalty: Insights from Retail Companies - Fendy Cuandra; Cory Carolyn; Lily Purwianti; Edy Yulianto Putra; Stefhani Susanto (UMSurabaya Publishing, 2026)
This study used PLS (Partial Least Squares) to examine and understand the factors that support and hinder e-customer loyalty on e-commerce websites. Research data was collected through a survey of 300 individuals who are actual consumers of e-commerce websites. The results of the PLS data analysis indicate that e-service quality has a significant positive influence on e-service satisfaction and e-service trust. It was also found that e-brand image has a strong positive influence on e-service satisfaction, e-service trust, and e-customer loyalty. Furthermore, it was determined that e-service satisfaction positively affects e-customer loyalty, whereas e-service trust does not. This study also shows that the overall quality of e-service, mediated by e-service satisfaction and e-service trust, has a substantial impact on e-customer loyalty, but the mediation path of e-service trust does not produce significant results. The conclusion that can be drawn is that to increase customer loyalty, e-commerce companies need to place more emphasis on improving service quality and good brand image, as well as paying attention to customer satisfaction. The recommendation is that companies should simultaneously strengthen service quality and brand image and prioritize these factors.